Measuring validity and reliability of website credibility factors in influencing user engagement questionnaire. Issue 1 (18th November 2020) - Saiful Bahry, Farrah Diana; Masrom, Maslin; Masrek, Mohamad Noorman
Abstract : Purpose: The purpose of this paper is to show the importance of validity process in survey questionnaire instrument development. It is to confirm all items chosen are valid in the context of study, especially in assessing municipal website Web user behaviours. The quality of measurement also can be assured. Design/methodology/approach: Several methods used to assess validity of the survey instrument in this study, such as face validity, content validity index (CVI) and construct validity. CVI assessment is widely used to examine each item in the survey instrument exact measures what is supposed to be measured. Prolific items used to evaluate web aesthetic, usability, navigation, content organization, interactivity and user engagement. Findings: Several items were rephrased and simplified during face validity assessment, while three items from user engagement construct were excluded after the CVI assessment. Reliability and redundancy analysis had shown good results for each item and construct for both dependent and independent variables. None of the items in any construct need to be eliminated. Research limitations/implications: The face validity, content validity and construct validity assessments are sufficient to assure the consistency of the conceptual framework, the content of items and overall measurement approach reflecting the setting or context of study which are web users. Practical implications: The validated survey instrument provides practical guidelines for government municipal website owners on how to stimulate website user to keep engaged on the government municipal website. Identified website content that acts as credibility cues can be as object attention when planning the strategy of Web content management. Through proper design and attracting touch up, the credibility cues can attract website user and force the user to engage deeper on the government municipal website content, believe it as the main source of information and recognize it as authoritative organization. Originality/value: The measurement model of this study that consists of formative construct of surface credibility, and user engagement is proposed to be tested in a different context of this study.